An analysis of the progress and hotspots of international research on the relationship between emotional intelligence and teacher leadership in the last 20 years based on citespace bibliometrics - Qianqian Suna; Mohd Khairuddin Abdullah @Jerry Abdullah; Tan, Choon Keong (Human Resource Management Academic Research Society, 2025)
This study explores the international trend of research on the relationship between emotional intelligence and teacher leadership, taps into the research hotspots in this field, and provides feasible references and insights for subsequent research. This study utilized citespace software to conduct bibliometric analysis of 632 relevant documents in the Web of Science Core Collection database in the past 20 years. The analysis was focused on publication trends, research institutions, authors, keyword co-occurrence, keyword clustering, timeline visualization and keyword mutation. The results showed a general upward trend in studies on emotional intelligence and teacher leadership over the past 20 years. The United States has the most publications, and the University System of Ohio leads among institutions, but its low centrality indicates weak global connectivity. The international research hotspots on emotional intelligence and teacher leadership in the last two decades are mainly in the areas of emotional intelligence and educational leadership, emotional intelligence and transformational leadership, emotional intelligence and social intelligence, and higher education. Through the keywords clustering visualization analysis, eight clusters were obtained: emotional intelligence, higher education, job satisfaction, teachers, competences, thematic analysis, social intelligence, and essential competencies. This suggests that the current research field is revolving around the themes of emotional intelligence, leadership, innovative approaches to education, and digital tools. The epidemic has had a major impact on research in the areas of emotional intelligence and educational methods. The study helps to learn about the progression, hotspots, and future directions for in-depth research on the relationship between emotional intelligence and teacher leadership, and provides a comprehensive understanding of the current status and development trends of research in this field.